Functional KCa3.1 K+ channels are required for human lung mast cell migration. Issue 10 (29th June 2006) - Cruse, G; Duffy, S M; Brightling, C E; Bradding, P
Abstract : Background: Mast cell recruitment and activation are critical for the initiation and progression of inflammation and fibrosis. Mast cells infiltrate specific structures in many diseased tissues such as the airway smooth muscle (ASM) in asthma. This microlocalisation of mast cells is likely to be key to disease pathogenesis. Human lung mast cells (HLMC) express the Ca 2+ activated K + channel KCa 3.1 which modulates mediator release, and is proposed to facilitate the retraction of the cell body during migration of several cell types. A study was undertaken to test the hypothesis that blockade of KCa 3.1 would attenuate HLMC proliferation and migration. Methods: HLMC were isolated and purified from lung material resected for bronchial carcinoma. HLMC proliferation was assessed by cell counts at various time points following drug exposure. HLMC chemotaxis was assayed using standard Transwell chambers (8 μm pore size). Ion currents were measured using the single cell patch clamp technique. Results: KCa 3.1 blockade with triarylmethane-34 (TRAM-34) did not inhibit HLMC proliferation and clotrimazole had cytotoxic effects. In contrast, HLMC migration towards the chemokine CXCL10, the chemoattractant stem cell factor, and the supernatants from tumour necrosis factor α stimulated asthmatic ASM was markedly inhibited with both the non-selective KCa 3.1 blocker charybdotoxin and the highly specific KCa 3.1 blocker TRAM-34 in a dose dependent manner. Although KCa 3.1 blockade inhibits HLMC migration, KCa 3.1 is not opened by the chemotactic stimulus, suggesting that it must be involved downstream of the initial receptor-ligand interactions. Conclusions: Since modulation of KCa 3.1 can inhibit HLMC chemotaxis to diverse chemoattractants, the use of KCa 3.1 blockers such as TRAM-34 could provide new therapeutic strategies for mast cell mediated diseases such as asthma.